Znaczenie religii dla trwałości małżeństwa i rodziny - Zbyrad, Teresa Jadwiga (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2021)
As the most significant social group, marriage and family are built on certain values. One of these fundamental values is religion. Throughout the centuries, the influence of religion in this respect has been enormous. Religion determined the form of marriage and family life: the regulation of sexual behaviour, the wedding ceremony, socialization of children, family functions, relations between parents and children, also including the place of the elderly in the family community. Modern society experiences a lot of threats to marriage and family life. The source of these is the progressive secularization of life. The research problem defined in this article boils down to showing the influence of religion on the life of marriage and family. Marriage and the family experience many changes due to the process of secularization. One of the risks is the fragility of marital bond and the potential breakdown of the family union. Therefore, the impact of religion on the stability of marriage and family is worth emphasising, along with due recognition of the extent to which religion constitutes a protective buffer against diverse threats from society.